Advanced transportation selected, peer reviewed papers from the 2011 International Conference on Civil Engineering and Transportation (ICCET 2011), 14-16 October, 2011, Jinan, China - Li, Shucai (TTP, Trans Tech Publications, 2011)
This collection, of contributions reviewed by international experts, covers: Road and Railway Engineering, Transportation Planning, Construction and Operation Organization, Modern Logistics System Planning and Optimization, Vehicle Engineering, Carrier Operation Engineering, ITS Theory and Applications, Traffic Control and Information Technology, Transportation and Social Economic Development, Low-Carbon Transportation Technology and Urban Transportation Planning and Management. It provides many valuable insights. Review from Book News Inc.: The first volume in this two-volume set from the Oct.
Keywords: Transportation engineering -- Congresses.; Highway engineering -- Congresses.; Railroad engineering -- Congresses.; Traffic engineering -- Congresses.; Motor vehicles -- Design and construction -- Congresses.; elektronické knihy; electronic books